Power-force-velocity profiling of sprinting athletes: methodological and practical considerations when using timing gates - Haugen, T. A.; Breitschädel, F.; Samozino, P. (The Journal of Strength and Conditioning Research, 2020)
The aim of this study was to investigate the impact of timing gate setup on mechanical outputs in sprinting athletes. Twenty-five male and female team sport athletes (mean ± SD: 23 ± 4 years, 185 ± 11 cm, 85 ± 13 kg) performed two 40-m sprints with maximal effort. Dual-beamed timing gates covered the entire running course with 5-m intervals. Maximal horizontal force (F0), theoretical maximal velocity (v0), maximal horizontal power (Pmax), force-velocity slope (SFV), maximal ratio of force (RFmax), and index of force application technique (DRF) were computed using a validated biomechanical model and based on 12 varying split time combinations, ranging from 3 to 8 timing checkpoints. When no timing gates were located after the 20-m mark, F0 was overestimated (mean difference, ±90% confidence level: 0.16, ±0.25 to 0.33, ±0.28 N/kg; possibly to likely; small), in turn affecting SFV and DRF by small to moderate effects. Timing setups covering only the first 15 m displayed lower v0 than setups covering the first 30-40 m of the sprints (0.21, ±0.34 to 0.25, ±0.34 m/s; likely; small). Moreover, poorer reliability values were observed for timing setups covering the first 15-20 m vs. the first 25-40 m of the sprints. In conclusion, the present findings showed that the entire acceleration phase should be covered by timing gates to ensure acceptably valid and reliable sprint mechanical outputs. However, only 3 timing checkpoints (i.e., 10, 20, and 30 m) are required to ensure valid and reliable outputs for team sport athletes.